Al-Shabaab and the sources of its resilience and resurgence: Cold War legacies and Jihadism in Somalia - Gardiner, Richard (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2018)
This study examines the continued development and survival of the group, Harakat al-Shabaab al-Mujahidin, commonly known as al-Shabaab "“ which emerged in 2006 as the militant wing of Somalia's Islamic Courts Union and became an independent group in 2007. The group has survived in spite of the fact that it has endured significant losses of personnel, resources and territory in Somalia. The study examines al-Shabaab's sources of resilience, resurgence and diversity. To achieve this, the study focused on the narratives of nine Somali nationals living and working in Durban, Grahamstown and Port Elizabeth, who fled their home country as a result of the ongoing violence and instability. Through understanding war as experience and placing the individual and community at the center of analysis, a people-centered approach is developed in understanding the organisation. This allows the study to challenge the state centered approaches to security and International Relations (IR) theory, which is important in the case of an armed, transnational, non-state actor such as al-Shabaab, whose operation and mobilisation requires no territorial base. The study makes use of social constructivism as a theoretical lens, as it provides an alternative way of analysing a non-state actor, specifically within an African context. The study argues that al-Shabaab's war within Somalia and East Africa is a territorial manifestation of a global phenomenon which highlights the importance of understanding its unique history within Somalia and East Africa. Importantly, the study also shows that veterans of the Afghan-Soviet war brought back ideas and tactics which have played a central part in shaping al-Shabaab's ideology and tactics. It is argued that al-Shabaab's process of decentralisation has ensured their survival but also alienated them from the Somali population. It is demonstrated that their insurgent tactics and process of intelligence gathering means that they operate in the shadows, making it difficult to locate them. Furthermore, the study shows that the role of regional actors and the presence of African Union peacekeepers have ensured that they have a constant enemy which provides a sense of cohesion and drive. The study concludes that al-Shabaab exists at a nexus of factors; its survival has and will depend on both domestic and transnational factors. Without the transnational nature of the organisation, al-Shabaab would not have become the organisation it is today. However, the future of al-Shabaab is heavily dependent on the security situation within Somalia. The immediate objectives of the group are focused within Somalia. Therefore, if the state institutions are consolidated within the country and human security levels improve, the organisation will struggle to operate with the same freedom it currently enjoys.
Keywords: Shabaab (Organization); Jihad; Cold War -- Influence; Cold War -- Social aspects -- Somalia; Somalia -- Foreign relations; Refugees, Somalian -- South Africa